The impact of Decree No. 99/2014/ND-CP for scientific and technological activities in Thai Nguyen University - Hong, Tran Thi (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
The article focuses on clarifying the impact of Decree No. 99/2014/ND-CP dated 20th October 2014 on science and technology (S&T) activities through two member universities of Thai Nguyen University after applying the Decree. From there, recommendations are made to limit the unwanted effects of the Decree to promote S&T activities in the university in the future. Code: 17082501